2019
DOI: 10.1080/23303131.2019.1569574
|View full text |Cite
|
Sign up to set email alerts
|

Retaining Social Workers: The Role of Quality of Work and Psychosocial Safety Climate for Work Engagement, Job Satisfaction, and Organizational Commitment

Abstract: The present study investigated how psychosocial safety climate (PSC), job demands (role conflict and work-family conflict), job resources (social support from superiors and social community at work), and assessments for quality of work relate to social workers' work engagement, job satisfaction, and organizational commitment. The results of the questionnaire study (N = 831) showed that quality of work was strongly related to all three outcomes, whereas PSC was found to be related to social workers' job satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
79
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 67 publications
10
79
0
4
Order By: Relevance
“…The nomological validity has been corroborated by operationalization of an extended JD-R model by the instrument with aspects of workability as outcome [11] as well as need for recovery [12] and also in relation to the newly introduced dimensions in the COPSOQ III of Work Engagement, Quality of Work [13] and Cyber Bullying [14]. Studies across different occupations have corroborated the internal consistency reliability and construct validity of the scales [11][12][13][15][16][17][18][19]. The ability to distinguish different groups (organizations with similar missions, work teams or occupational groups) has been demonstrated [20][21][22], as also the relevance of multilevel analyses and for intervention and organizational change studies [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The nomological validity has been corroborated by operationalization of an extended JD-R model by the instrument with aspects of workability as outcome [11] as well as need for recovery [12] and also in relation to the newly introduced dimensions in the COPSOQ III of Work Engagement, Quality of Work [13] and Cyber Bullying [14]. Studies across different occupations have corroborated the internal consistency reliability and construct validity of the scales [11][12][13][15][16][17][18][19]. The ability to distinguish different groups (organizations with similar missions, work teams or occupational groups) has been demonstrated [20][21][22], as also the relevance of multilevel analyses and for intervention and organizational change studies [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 88%
“…An iterative process including translation-back-translation procedures and cognitive interviewing methods supported the face and content validity, as well as the cross-cultural equivalency of COPSOQ II and COPSOQ III test items [8][9][10]. The nomological validity has been corroborated by operationalization of an extended JD-R model by the instrument with aspects of workability as outcome [11] as well as need for recovery [12] and also in relation to the newly introduced dimensions in the COPSOQ III of Work Engagement, Quality of Work [13] and Cyber Bullying [14]. Studies across different occupations have corroborated the internal consistency reliability and construct validity of the scales [11][12][13][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 90%
“…Abundant previous studies were found on the antecedents of employees' OC in various contexts (Lambert et al, 2018;Luz et al, 2018;Pathak & Tripathi, 2010;Top et al, 2015). Several variables received great attention from previous researchers, such as different leadership styles (Chen et al, 2019;Choi et al, 2015b;Gul et al, 2012), employees' burnout (Sarisik et al, 2019), job related variables like job security and work style (Pathak & Tripathi, 2010;Spanuth & Wald, 2017), job characters (Coetzer & Rothmann, 2006), employee training and teamwork (Hanaysha, 2016a), environment and organizational learning (Hanaysha, 2016b), psychosocial safety climate (Geisler et al, 2019), corporate values, and corporate social responsibility (Asrar-ul-Haq et al, 2017;Obalola et al, 2012). However, few studies probe deeply into the impact of ethics variables on OC of employees in Chinese context where employees and managers may confront different ethical situations from other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Degree of quality of work, in terms of workers’ perceptions of the level of quality in the services provided, has been reported to have a beneficial relationship to workers’ job performance (McHugh and Stimpfel, 2012), job satisfaction, work engagement, and organizational commitment (Geisler et al, 2019), health and turnover (Castle and Engberg, 2005; Astvik and Melin, 2012). The relevance of attending to service quality as a positive outcome in JD-R research has been noted (Schaufeli and Taris, 2014).…”
Section: Introductionmentioning
confidence: 99%